Efeitos subjetivos do processo de trabalho vivenciados por profissionais em um Centro de Atenção Psicossocial Álcool e Drogas - Wandekoken, Kallen Dettmann (2015)
This thesis presents the results of a research that aimed to analyze how workers experience the subjective effects produced by the work process in a Psychosocial Care Center Alcohol and Drugs (CAPSad in Portuguese). The research was conducted under a qualitative approach, in a service of Vila Velha, Espírito Santo State, Brazil . The data was collected through five steps: 1. Desk review of existing policies about drug use; 2. Analysis of medical records; 3. group interview with ten employees; 4. Eighty hours of observation of daily work; 5. In-depth interview with thirteen workers. For data analysis, we used the thematic analysis technique.We conclude that in the analyzed policies, has prevailed ideas related to the users repression, despite the attempt of the Ministry of Health (MS in Portuguese), which considers the harm reduction as a strategy that values the person and their uniqueness.The analysis also pointed out the difficulties faced by workers from that city to act in accordance to the MS guidelines, since the municipal actions has emphasized repression, religious approach and intimidation as a prevention strategy, with the agreement of justice and police. We emphasize that the ambiguities have repercussions at work and for the worker. We also point out other aspects that generate effects on workers: poor working conditions (due to the service structure, low wages and non-existent care network), lack of recognition (due to management failure and the lack of standards) and work overload (due the lack of professionals and conflicts in the activities division).These situations lead to subjective effects such as exhaustion, illness, fear, inability to act, apathy, devaluation, lack of motivation and worker's imprisonment.These effects are all negative and workers has experienced them through emotional detachment in work process, which negatively affects the possibility of producing an effective care.We suggest investments in employee training, with a focus on permanent education, since it causes learning encouragement and creative positioning in face of experienced effects in daily life.There is the needfor dialogue, between workers and management, between the workers themselves and between workers and users.